Importance of color stability of the esthetic restoration materials - Basudan, Thuraya Abdulrahim; Bahshan, Ibrahim Alhosain; Almutairi, Mohammed Khashman; Alkadi, Nwaf Ahmed; Al Qiriaqri, Jehad Aymen; Alkhudhair, Hazem Ibrahim; Al Khunein, Yazeed Abdulaziz; Alzurqi, Nada Ibrahim; Jammaz, Abdullah Ibrahim Bin; Alshahrani, Amani Awdah; Alsaad, Tariq Mohammad (International Journal Of Community Medicine And Public Health, 2021)
Color stability has a vital role in several factors. Including the cosmetic appearance, confidence while smiling, and facial emotions, and in some patients, it denoted healthy and vital dental health. Dental discoloration denotes the lack of dental care. This varies from excessive use of external artificial coloration materials such as coffee, tea, and fizzy drinks. Also, in some cases, the dental discoloration is due to internal pathological conditions or due to medical treatments usage. Radiation has been remarked as one of the causes that cause dental discoloration. In addition to that, chemotherapy was also associated with dental discoloration. Some medications, such as tetracycline and antihistamines, were linked to dental discoloration. The literature discussed in-vitro experiments for the substances affecting the teeth' color status. Coffee was the most significant cause for dental discoloration, either human use (in-vivo) or laboratory experiments (in-vitro). The sociodemographic status was linked to the variance of dental discoloration. Future recommendations are concerned about the public health sector. The WHO should offer comprehensive dental care for all people all over the world, and not exclusive for specific socioeconomic areas. Practical plans for screening dental pathologies should be investigated and for systematic pathologies that might be associated with dental issues.